(untitled) - FAO (Rome, Italy, 1996)
The book reviews the progress made in improving street-food quality and safety at a global level; analyses different experiences and lessons learned; and provides the international community with an updated set of recommandations and guidelines to simulate and enable new and continuing improvements
Keywords: food supply,hygiene, public